2014
DOI: 10.1039/c4ra04687k
|View full text |Cite
|
Sign up to set email alerts
|

Recalcitrance of cyanuric acid to oxidative degradation by OH radical: theoretical investigation

Abstract: Electron deficiency of the triazine ring makes the reactions between cyanuric acid and OH radical energetically unfavorable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…could then confer its recalcitrance toward hydroxyl radical attack. In the same way, cyanuric acide is well known as recalcitrant to hydroxyl radical oxidation due to the electron deficiency of the triazine ring linked to the higher electronegativity of nitrogen compared to that of carbon (Liu, 2014).…”
Section: Evolution Of Mtz Degradation and Mineralizationmentioning
confidence: 99%
“…could then confer its recalcitrance toward hydroxyl radical attack. In the same way, cyanuric acide is well known as recalcitrant to hydroxyl radical oxidation due to the electron deficiency of the triazine ring linked to the higher electronegativity of nitrogen compared to that of carbon (Liu, 2014).…”
Section: Evolution Of Mtz Degradation and Mineralizationmentioning
confidence: 99%
“…43,44 However, whether the radicals generated in the UV 222 /Cl-cyanurates AOP increase the concentrations of byproducts remains unknown. Although cyanuric acid and Cl-cyanurates are inert to radicals (HO • , Cl • , and ClO • ), 37,45 whether UV 222 irradiation can destruct cyanuric acid and Clcyanurates to generate undesired byproducts remains to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Only H atom abstraction reactions were considered, in order to illustrate the effect of direct electron transfer on OH • reactivity, although other reaction mechanisms are likely occurring (e.g., OH • addition). Simulations with CA were chosen because it was reported to have the lowest measured reaction rate constant with OH • . ,, …”
Section: Resultsmentioning
confidence: 99%
“…Simulations with CA were chosen because it was reported to have the lowest measured reaction rate constant with OH • . 47,48,50 Results from DFT simulations determined that ΔG r = 226 kJ mol −1 for reaction 13 and ΔG r = −206 kJ mol −1 for reaction 14. These results indicated that the direct oxidation reaction to produce CA •+ allowed for a thermodynamically favorable reaction with OH • , which explained the complete mineralization of ATZ observed in our experiments.…”
Section: Mechanism For Atz and Cdn Electrochemicalmentioning
confidence: 99%